1986
DOI: 10.1111/j.1536-7150.1986.tb01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Leon Walras' Theory of Money

Abstract: Leon Walras'iheory of money, in spite of its serious flaws, provides important insights which should prove of interest to modern monetarists. He was one of the few economists in the classical tradition to detect major deficiencies in the quantity theory of money. He favored a strong public policy to regulate the money supply in order to ensure the preservation of economic equilibrium. Most of his arguments were motivated by his concern for the wage earners because he knew that they were the first to suffer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…He was also able to incorporate capital and growth as well as introduce the concept of money in his analysis (Walras, 1874). Cirillo (1986) claims that Walras "demonstrated that a pure system of money was consistent with his general equilibrium analysis" and that he "indirectly . .…”
Section: Marginalism and Opportunity Costsmentioning
confidence: 96%
“…He was also able to incorporate capital and growth as well as introduce the concept of money in his analysis (Walras, 1874). Cirillo (1986) claims that Walras "demonstrated that a pure system of money was consistent with his general equilibrium analysis" and that he "indirectly . .…”
Section: Marginalism and Opportunity Costsmentioning
confidence: 96%
“…Stabiliser la valeur de la monnaie est indispensable pour la préservation de l'équilibre économique. Il prône alors une intervention étatique (Cirillo, 1986) et propose le système suivant. L'économie dispose d'une monnaie-marchandise, l'or.…”
Section: La Question De La Nature De L'offre De Monnaieunclassified
“…As Plumwood argues, dualism embeds hierarchy by denying the superior's dependency on the inferior, objectifying the inferior in terms of its usefulness to the superior, and homogenizing the inferior group [18] (pp. [48][49][50][51][52][53][54].…”
Section: Western Ontology As a Mechanical Dualismmentioning
confidence: 99%
“…The model homogenizes the circular, wage, and slave labor embedded in commodities and productive inputs [46] and [47] (pp. [46][47][48][49][50][51][52][53][54][55] and disembodies labor from its biological function [1] (p. 130). From a resource perspective, commodities are viewed in terms of a "mechanistic ontology" [48] (p. 11) with no inherent value until labor or capital actualize their value in the form of producer profit or consumer utility [11] (p. 192) [18] (p. 111).…”
Section: Orthodox Economics As Dualistic Ontologymentioning
confidence: 99%
See 1 more Smart Citation